Delivering cognitive therapy for adolescent social anxiety disorder in NHS CAMHS: a qualitative analysis of the experiences of young people, their parents and clinicians-in-training - Taylor, L; Creswell, C; Pearcey, S; Brooks, E; Leigh, E; Stallard, P; Waite, P; Clark, DM; Stephens, G; Larkin, M (Cambridge University Press, 2021)
Background: Social anxiety disorder (SAD) is common. It usually starts in adolescence, and without treatment can disrupt key developmental milestones. Existing generic treatments are less effective for young people with SAD than with other anxiety disorders, but an adaptation of an effective adult therapy (CT-SAD-A) has shown promising results for adolescents.